2015
DOI: 10.1097/01.j.pain.0000460314.73358.ff
|View full text |Cite
|
Sign up to set email alerts
|

Variability in opioid prescription monitoring and evidence of aberrant medication taking behaviors in urban safety-net clinics

Abstract: Little is known about variability in primary care providers’ (PCPs) adherence to opioid-monitoring guidelines for patients. We examined variability of adherence to monitoring guidelines among PCPs and ascertained the relationship between PCP adherence and opioid misuse by their patients. We included primary care patients receiving long-term opioids (≥3 prescriptions within 6 months) for chronic noncancer pain and PCPs with ≥4 eligible patients. We examined guideline adherence using: (1) electronic health recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 18 publications
(22 reference statements)
2
21
0
Order By: Relevance
“…Baseline characteristics of patients at three of the four participating sites have been published elsewhere (Khalid, et al, 2014; Lange, et al, 2015). At the adult primary care practice at Boston Medical Center, 42% of patients had ever had a controlled substance agreement, 64% had any urine drug testing in the past year, and 32% had at least two early refills of opioids in the past year.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline characteristics of patients at three of the four participating sites have been published elsewhere (Khalid, et al, 2014; Lange, et al, 2015). At the adult primary care practice at Boston Medical Center, 42% of patients had ever had a controlled substance agreement, 64% had any urine drug testing in the past year, and 32% had at least two early refills of opioids in the past year.…”
Section: Resultsmentioning
confidence: 99%
“…Our definitions are based on outcomes from our prior studies and from other published literature (Hariharan, et al, 2007; Khalid et al, 2014; Lange et al, 2015; Reid, et al, 2002; Starrels, et al, 2011). A blinded data analyst will extract all study outcomes and exploratory variables from a clinical data warehouse.…”
Section: Methodsmentioning
confidence: 99%
“…However, no randomized trial evaluated opioid abuse, addiction, or related outcomes with long‐term opioid therapy versus placebo or nonopioid therapy. In fact, a higher variability exists in the proposed long‐term use monitoring systems …”
Section: Discussionmentioning
confidence: 99%
“…28 Similarly, only one patient between both groups had any documentation that a urine drug screen was utilized, consistent with prior work that providers infrequently order urine drug screens, though more recent studies show this may be improving. 9, 10, 29 …”
Section: Discussionmentioning
confidence: 99%
“…Little is known about how providers make decisions about opioid dosing (i.e., to continue, increase, or decrease a patient’s dose) when they write individual prescriptions. Prior studies examining risk factors for high-dose opioid use and opioid misuse have found that documentation of guideline-concordant practices for safe opioid prescribing is poor; 9, 10, 11, 12, 13 however, neither providers’ rationale for individual opioid prescriptions nor encounter-level factors associated with opioid dose increases have been previously studied.…”
Section: Introductionmentioning
confidence: 99%